(untitled) (Advances in Knowledge Representation, 2021)
This article contributes to the introduction to the study of ontology, an interdisciplinary research field, which, in the context of information systems, has contributed to the modeling and development of intelligent systems. It is a research theme in several areas, such as Computer Science, Information Science, Philosophy, Artificial Intelligence, Linguistics, Knowledge Management, to name a few. It is also applied in various fields of knowledge, in particular, in Biomedicine. In addition to scientific research, we observed that it is also necessary to disseminate and popularize the ontology practices in Brazil, and then the approach here is pragmatic. We discuss real ontology initiatives and applications in Biomedicine, a domain in which ontological artifacts have been successfully applied for at least 20 years.